Mixturopoda Baker and Monson, a new genus of the uropodine family Metagynuridae (Acari: Mesostigmata) from the British Isles - Baker, Anne S.; Monson, Frank D. (Zootaxa, 2007)
A new taxon of mesostigmatid mite of the suborder Uropodina is described from damp, rotten straw associated with Dutch barns in NW England. Mixturopoda evansi gen. nov., sp. nov. possesses character states that have not previously been recorded in uropodines, e.g., the female genital shield bears setae st5 and is located behind coxae IV but not within the ventral shield, and barsitarsi II–IV lack seta pd3. Other states are a combination of those used to diagnose currently recognized superfamilies, e.g., subcylindrical, separated coxae I that are inserted in the gnathopodal cavity, absence of pedofossae and paragynial shields, and adult dorsal and marginal shields and deutonymphal dorsal shield undivided. Mixturopoda evansi is placed in the family Metagynuridae on the basis of the posterior position of the female genital shield. Amendments to the diagnoses of the Metagynuridae and its type genus, Metagynella, are proposed.